Reduced laughter : seriocomic features and their functions in the Book of Kings - Paynter, Helen. (Biblical Interpretation Series, 2016)
In this book Helen Paynter offers a radical re-evalution of the central section of Kings. Reading with attention to the literary devices of carnivalization and mirroring, she demonstrates that it contains a florid satire on kings, prophets and nations. Building on the work of humorists, literary critics and biblical scholars, the author constructs diagnostic criteria for carnivalization (seriocomedy), and identifies an abundance of these features within the Elijah/Elisha and Aram narratives, showing how literary mirroring further enhances their satirical effect. This book will be of particular interest to students and scholars concerned with the Hebrew Bible as literature but will be valued by those who favour more historical approaches for its insights into the Hebrew text.